A Novel Modeling for Assessing Frequency Behavior During a Hydro-to-Thermal Plant Black Start Restoration Test - Roberto Benato; Gianluca Bruno; Sebastian Dambone Sessa; Giorgio Maria Giannuzzi; Luca Ortolano; Gianni Pedrazzoli; Michele Poli; Francesco Sanniti; Roberto Zaottini (IEEE Access, 2019)
Northern electric grid of Italy was involved in a black start mock drill. This test took place on November 2016 in order to check the coordination and efficiency of all the operational staffs and the automatic regulators involved in the case of a real blackout scenario. This paper presents the results of a research carried out in collaboration with Terna Rete Italia (the Italian Transmission System Operator), in order to find strengths and weaknesses and eventually to upgrade the existing restoration plan. Starting from the measures coming from generating plants and substations bars, the model of frequency regulation system for both the participating hydro and thermal power plants is developed. This work gives the system operator an essential tool to understand many complex dynamics and phenomena occurred during the test. At the same time, a robust model simulating the system behavior with different grid configurations is presented: it gives the opportunity to enhance both the classical power system control theory and the black start practices.